Optical Parameters of Atomically Heterogeneous Systems Created by Plasma Based Low Energy Ion Beams: Wavelength Dependence and Effective Medium Model - Singh, Krishn Pal; Bhattacharjee , Sudeep (Frontiers in Physics, 2021)
The present article presents the irradiation effects of low energy (~ 0.5 keV) inert gaseous Argon ion beams on optical constants (real (n) and imaginary (k) parts of the refractive index), dielectric constants, skin depth, and optical conductivity of copper (Cu), silver (Ag), and aluminum (Al) metallic thin films (MTF). The optical constants of pristine MTF are obtained by employing the universal Kramers-Kronig (KK) technique. The reflectivity of pristine MTF measured using UV-VIS-NIR spectrophotometry is used as an input parameter in the KK technique to determine the optical constants as a function of energy (or wavelength (lambda)) of incident light ranging between ~ 1-4.96 eV (or 250-1200 nm). For the irradiated MTF, the optical constants including the skin depth (delta = lambda/ 2 pi k), optical conductivity (sigma = nkc/ lambda), and dielectric constants (epsilon_{1} = n^{2} - k^{2} and} epsilon_{2} = 2 n k) with varying ion fluence have been investigated by implementing the Maxwell-Garnett (MG) approximation, used to determine the effective dielectric constants of a random mixture of two different mediums. Additionally, n and k obtained from MG approximation have been compared with those obtained using the pseudo- Brewster angle technique for four different laser wavelengths (405, 532, 632.8 and 670 nm) and are found to be in good agreement with each other. It is observed that the optical constants and optical conductivity of the MTF decrease with increase in ion beam fluence, while the skin depth increases. Besides the optical constants, the behavior of skin depth, dielectric constants, and optical conductivity of the irradiated MTF with varying fluence are discussed in this article.